2020
DOI: 10.3847/1538-4357/ab65f5
|View full text |Cite
|
Sign up to set email alerts
|

NuSTAR Perspective on High-redshift MeV Blazars

Abstract: With bolometric luminosities exceeding 10 48 erg s −1 , powerful jets and supermassive black holes at their center, MeV blazars are some of the most extreme sources in the Universe. Recently, the Fermi-Large Area Telescope detected five new γ-ray emitting MeV blazars beyond redshift z = 3.1. With the goal of precisely characterizing the jet properties of these extreme sources, we started a multiwavelength campaign to follow them up with joint NuSTAR, Swift and SARA observations. We observe six high-redshift qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 110 publications
2
23
0
Order By: Relevance
“…With finer sampling (3 days), this increases to ≈ 10 49 erg s −1 , but TS falls below 25, TS 20. The SED in the γ-ray region is very steeply decreasing power law (α ≈ 2) as expected for strong external inverse Compton cooling from the existence of the luminous quasar environment that was described in the last section (Sahakyan et al 2020;Marcotulli et al 2020). This combined with the high redshift indicates that most of the γ-ray luminosity is most likely at observed energies < 0.1 GeV.…”
Section: γ-Ray Behaviorsupporting
confidence: 62%
See 2 more Smart Citations
“…With finer sampling (3 days), this increases to ≈ 10 49 erg s −1 , but TS falls below 25, TS 20. The SED in the γ-ray region is very steeply decreasing power law (α ≈ 2) as expected for strong external inverse Compton cooling from the existence of the luminous quasar environment that was described in the last section (Sahakyan et al 2020;Marcotulli et al 2020). This combined with the high redshift indicates that most of the γ-ray luminosity is most likely at observed energies < 0.1 GeV.…”
Section: γ-Ray Behaviorsupporting
confidence: 62%
“…There is no observational evidence to justify a model more complicated than a homogeneous, spherical, single zone of plasma. Single zone spherical models are a standard technique even in blazar jet calculations out of practical necessity including previous treatments of this source (Ghisellini et al 2010;Sahakyan et al 2020;Marcotulli et al 2020). A simple homogeneous spherical volume model or plasmoid has historically provided an understanding of the spectra and the time evolution of astrophysical radio sources (van der Laan 1966).…”
Section: A Physical Model Of the North Lobe Ssa Power Lawmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have tentatively explored absorption scenarios, either neutral or a warm absorption component, as a minor part of their work, typically placing the absorber at the blazar redshift (e.g. Bottacini et al 2010;Paliya et al 2016;Ricci et al 2017;Marcotulli et al 2020;Haim et al 2019). Bottacini et al (2010) found they could not constrain their photo-ionized model parameter better than an upper limit.…”
Section: Discussion a N D C O M Pa R I S O N W I T H Ot H E R S T U D I E Smentioning
confidence: 99%
“…We reviewed literature that studied large numbers of blazars (e.g. Perlman et al 1998;Donato, Sambruna & Gliozzi 2005;Eitan & Behar 2013;Ighina et al 2019;Marcotulli et al 2020) and, within our criteria, selected objects randomly for our sample. Our sample has 14 with z > 2, a high fraction of the total available as noted above.…”
Section: Data S E L E C T I O N a N D M E T H O D O L O G Ymentioning
confidence: 99%